Evaluation of the situation of regular tax in Algeria in light of tax reforms Analytical study during the period 2009-2019 - Ben Latrech , Mouloud (Journal of Research in Finance and Accounting, 2026)
This study deals with the issue of the regular tax in Algeria in light of the tax reforms, and to show the impact of the tax reform, which aims to improve the financial return of the tax system, and to research the possibility of replacing the regular tax with the petroleum tax By analyzing the actual financial outcome of the tax system, the results of the study indicated that there is a gap between the regular tax and the petroleum tax, which prompts the state to take more measures and reforms to the tax system and activate it. Among these measures, which can contribute to improving the financial return of the tax system and reducing the gap between the regular tax and the petroleum tax, are economic diversification, digitization of fiscal procedures, completion of structural reforms between sectors and transparency of commercial transactions.